RUANG LINGKUP HUKUM ISLAM - Muhammad Kurniawan Budi Wibowo (MAMBA'UL 'ULUM, 2021)
This study describes Islamic law and its scope. This research uses a qualitative approach with descriptive research type. Data analysis using descriptive analysis. The process is carried out since the data, so that when in the field, researchers have started the data analysis process until the end of the research. This research concludes that etymologically Islamic law is all kinds of provisions or provisions regarding something in which the provisions have been regulated and stipulated by Islam. The scope of Islamic law is divided into two, namely 1) law relating to matters of worship, and 2) law relating to social matters. In addition, there is a study of the principles of Islamic law. The value of the divine value is implemented into a number of basic principles or as a more concrete one in a number of fields of Islamic law. As well as the objectives of Islamic law are not limited in terms of material alone, but far in the future pay attention to all aspects, material, immaterial, individuals, society, and humanity in general. The last one regarding the sources of Islamic law. The sources of Islamic law are Al-Qur'an, Al-haditht, and Ar-ra'yu (reasoning).